Cancer diagnosis disclosure from Portuguese physicians. Issue 4 (27th August 2014) - Oliveira, Lucília; Fernandes, Marta; Santos, Zulmira; Bastos, Hugo; Cabral, Ana
Abstract Objective: Doctor–patient communication in oncology, particularly concerning diagnostic disclosure, is a crucial factor related to the quality of the doctor–patient relationship and the psychological state of the patient. The aims of our study were to investigate physicians' opinions and practice with respect to disclosure of a cancer diagnosis and to explore potential related factors. Method: A self-report questionnaire developed for our study was responded to by 120 physicians from Coimbra University Hospital Centre and its primary healthcare units. Results: Some 91.7% of physician respondents generally disclosed a diagnosis, and 94.2% were of the opinion that the patient knowing the truth about a diagnosis had a positive effect on the doctor–patient relationship. A need for training about communicating with oncology patients was reported by 85.8% of participants. The main factors determining what information to provide to patients were: (1) patient intellectual and cultural level, (2) patient desire to know the truth, and (3) the existence of family. Significance of results: Our results point to a paradigm shift in communication with cancer patients where disclosure of the diagnosis should be made part of general clinical practice. Nevertheless, physicians still experience difficulties in revealing cancer diagnoses to patients and often lack the skills to deal with a patient's emotional responses, which suggests that more attention needs to be focused on communication skills training programs.